2019
DOI: 10.1371/journal.pone.0226854
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin-I is a critical modulator in non-alcoholic steatohepatitis (NASH)

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a progressive liver disease characterized by dysregulated lipid metabolism and chronic inflammation ultimately resulting in fibrosis. Untreated, NAFLD may progress to non-alcoholic steatohepatitis (NASH), cirrhosis and death. However, currently there are no FDA approved therapies that treat NAFLD/NASH. Thrombospondin-I (TSP-1) is a large glycoprotein in the extracellular matrix that regulates numerous cellular pathways including transforming growth factor beta 1 (TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 48 publications
3
46
1
Order By: Relevance
“…Recently, elevated hepatic expression of another thrombospondin family, TSP1 , has been reported in NAFLD patients and mice 21,22 . However, serum TSP1 data from human serum are limited, 23 and no studies have widely examined the correlations between serum TSP1 levels and NAFLD histopathology, including ballooning grade and fibrosis stage.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, elevated hepatic expression of another thrombospondin family, TSP1 , has been reported in NAFLD patients and mice 21,22 . However, serum TSP1 data from human serum are limited, 23 and no studies have widely examined the correlations between serum TSP1 levels and NAFLD histopathology, including ballooning grade and fibrosis stage.…”
Section: Resultsmentioning
confidence: 99%
“…Discussion TSP1 is a multifunctional secreted matricellular protein and has been involved in the pathogenesis of many diseases such as cardiovascular disease, renal complications, obesity and insulin resistance. However, the role of TSP1 in the non-alcoholic fatty liver disease (NAFLD)/ non-alcoholic steatohepatitits (NASH) is largely unknown 16,17 . In this study, by utilization of tissue specific TSP1 knockout mice, we demonstrate that macrophage-specific TSP1 deletion but not adipocyte-specific TSP1 deletion protects mice against obesity-associated liver injury, accompanied by reduced liver inflammation and fibrosis.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…In addition to regulating liver macrophage pro-inflammatory status as discussed above, through paracrine effects, macrophage-derived TSP1 may directly modulate the function of other liver cells such as hepatocyte, stellate cells or sinusoidal endothelial cells and impact the development and progression of NAFLD/NASH 17,47,48 . It has been shown that TSP1 inhibition or knockdown in cultured stellate cell attenuated TGF-β -induced stellate cell activation (e.g.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 2 more Smart Citations